Chemically Stable Metal-Organic Frameworks: Rational Construction and Application Expansion - He, Tao; Kong, Xiang-Jing; Li, Jian-Rong (Accounts of chemical research, 2021)
Metal-organic frameworks (MOFs) have been attracting tremendous attention owing to their great structural diversity and functional tunability. Despite numerous inherent merits and big progress in the fundamental research (synthesizing new compounds, discovering new structures, testing associated properties, etc.), poor chemical stability of most MOFs severely hinders their involvement in practical applications, which is the final goal for developing new materials. Therefore, constructing new stable MOFs or stabilizing extant labile MOFs is quite important. As with them, some "potential" applications would come true and a lot of new applications under harsh conditions can be explored. Efficient strategies are being pursued to solve the stability problem of MOFs and thereby achieve and expand their applications.In this Account, we summarize the research advance in the design and synthesis of chemically stable MOFs, particularly those stable in acidic, basic, and aqueous systems, as well as in the exploration of their applications in several expanding fields of environment, energy, and food safety, which have been dedicated in our lab over the past decade. The strategies for accessing stable MOFs can be classified into: (a) assembling high-valent metals (hard acid, such as Zr4+, Al3+) with carboxylate ligands (hard base) for acid-stable MOFs; (b) combining low-valent metals (soft acid, such as Co2+, Ni2+) and azolate ligands (soft base, such as pyrazolate) for alkali-resistant MOFs; (c) enhancing the connectivity of the building unit; (d) contracting or rigidifying the ligand; (e) increasing the hydrophobicity of the framework; and (f) substituting liable building units with stable ones (such as metal metathesis) to obtain robust MOFs. In addition, other factors, including the geometry and symmetry of building units, framework-framework interaction, and so forth, have also been taken into account in the design and synthesis of stable MOFs. On the basis of these approaches, the stability of resulting MOFs under corresponding conditions has been remarkably enhanced.With high chemical stability achieved, the MOFs have found many new and significant applications, aiming at addressing global challenges related to environmental pollution, energy shortage, and food safety.A series of stable MOFs have been constructed for detecting and eliminating contaminations. Various fluorescent MOFs were rationally customized to be powerful platforms for sensing hazardous targets in food and water, such as dioxins, antibiotics, veterinary drugs, and heavy metal ions. Some hydrophobic MOFs even showed effective and specific capture of low-concentration volatile organic compounds.Novel MOFs with record-breaking acid/base/nucleophilic regent resistance have expanded their application scope under harsh conditions. BUT-8(Cr)A, as the most acid-stable MOF yet, showed reserved structural integrity in concentrated H2SO4 and recorded high proton conductivity; the most alkali-resistant MOF, PCN-601, retained crystallinity even in boiling saturated NaOH aqueous solution, and such base-stable MOFs composed of non-noble metal clusters and poly pyrazolate ligands also demonstrated great potential in heterogeneous catalysis in alkaline/nucleophilic systems for the first time.It is believed that this Account will provide valuable references on stable MOFs' construction as well as application expansion toward harsh conditions, thereby being helpful to promote MOF materials to step from fundamental research to practical applications.Metal-organic frameworks (MOFs) have been attracting tremendous attention owing to their great structural diversity and functional tunability. Despite numerous inherent merits and big progress in the fundamental research (synthesizing new compounds, discovering new structures, testing associated properties, etc.), poor chemical stability of most MOFs severely hinders their involvement in practical applications, which is the final goal for developing new materials. Therefore, constructing new stable MOFs or stabilizing extant labile MOFs is quite important. As with them, some "potential" applications would come true and a lot of new applications under harsh conditions can be explored. Efficient strategies are being pursued to solve the stability problem of MOFs and thereby achieve and expand their applications.In this Account, we summarize the research advance in the design and synthesis of chemically stable MOFs, particularly those stable in acidic, basic, and aqueous systems, as well as in the exploration of their applications in several expanding fields of environment, energy, and food safety, which have been dedicated in our lab over the past decade. The strategies for accessing stable MOFs can be classified into: (a) assembling high-valent metals (hard acid, such as Zr4+, Al3+) with carboxylate ligands (hard base) for acid-stable MOFs; (b) combining low-valent metals (soft acid, such as Co2+, Ni2+) and azolate ligands (soft base, such as pyrazolate) for alkali-resistant MOFs; (c) enhancing the connectivity of the building unit; (d) contracting or rigidifying the ligand; (e) increasing the hydrophobicity of the framework; and (f) substituting liable building units with stable ones (such as metal metathesis) to obtain robust MOFs. In addition, other factors, including the geometry and symmetry of building units, framework-framework interaction, and so forth, have also been taken into account in the design and synthesis of stable MOFs. On the basis of these approaches, the stability of resulting MOFs under corresponding conditions has been remarkably enhanced.With high chemical stability achieved, the MOFs have found many new and significant applications, aiming at addressing global challenges related to environmental pollution, energy shortage, and food safety.A series of stable MOFs have been constructed for detecting and eliminating contaminations. Various fluorescent MOFs were rationally customized to be powerful platforms for sensing hazardous targets in food and water, such as dioxins, antibiotics, veterinary drugs, and heavy metal ions. Some hydrophobic MOFs even showed effective and specific capture of low-concentration volatile organic compounds.Novel MOFs with record-breaking acid/base/nucleophilic regent resistance have expanded their application scope under harsh conditions. BUT-8(Cr)A, as the most acid-stable MOF yet, showed reserved structural integrity in concentrated H2SO4 and recorded high proton conductivity; the most alkali-resistant MOF, PCN-601, retained crystallinity even in boiling saturated NaOH aqueous solution, and such base-stable MOFs composed of non-noble metal clusters and poly pyrazolate ligands also demonstrated great potential in heterogeneous catalysis in alkaline/nucleophilic systems for the first time.It is believed that this Account will provide valuable references on stable MOFs' construction as well as application expansion toward harsh conditions, thereby being helpful to promote MOF materials to step from fundamental research to practical applications.